Sales performance of hotel industry in Malaysia, case study: Grand Seasons Hotel / Nurliza Mohammad Safar (Faculty of Business and Management, 2007)
The Grand Season Hotel is managed by Metroplex Holding Sdn Bhd-Leisure Division. Metroplex Holding Sdn Bhd is a wholly subsidiary of Metroplex as public listed company. It has 800 hotels room and situated along Jalan Pahang just of Jalan Tun Razak. The hotel starts it operation since 14 July 1998 and was recognized as the tallest hotel in Malaysia, which was written in the Malaysia Book of Record. Good Decisions require managers' understanding of the response function relating to the sales performance. Managers are principally concerned with the allocation of scare resources such as sales force, advertising and promotion, for the purpose improving the market and profit performance of their product or brand. Performance studies greatly contribute to both business and academic discussion, giving important insights about real success of a company. Basing on these studies, managers can evaluate the success of their firm generally or in a certain part of a business and to come to conclusions that benefit the firm in both short and long term.